2014
DOI: 10.1073/pnas.1314787111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of dynamical downscaling in agricultural impacts projections

Abstract: Interest in estimating the potential socioeconomic costs of climate change has led to the increasing use of dynamical downscalingnested modeling in which regional climate models (RCMs) are driven with general circulation model (GCM) output-to produce fine-spatial-scale climate projections for impacts assessments. We evaluate here whether this computationally intensive approach significantly alters projections of agricultural yield, one of the greatest concerns under climate change. Our results suggest that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 51 publications
(44 reference statements)
2
55
0
Order By: Relevance
“…Any climate change assessment where the GCM outputs are used as input will inherit the biases in the subsequent outputs. Studies on climate change impacts on land surface hydrology and agriculture report that models forced with outputs directly from the GCMs or even regional climate models nested within GCMs result in unacceptably biased simulations, and therefore, the GCM (or regional model) outputs ought to be bias corrected [ Glotter et al , ; Salathé et al , ; Sulis et al , ; Wood et al , ]. Since the model outputs cannot be used directly, we apply bias correction that corrects all moments of the climate fields' statistical distribution at monthly scale.…”
Section: Discussionmentioning
confidence: 99%
“…Any climate change assessment where the GCM outputs are used as input will inherit the biases in the subsequent outputs. Studies on climate change impacts on land surface hydrology and agriculture report that models forced with outputs directly from the GCMs or even regional climate models nested within GCMs result in unacceptably biased simulations, and therefore, the GCM (or regional model) outputs ought to be bias corrected [ Glotter et al , ; Salathé et al , ; Sulis et al , ; Wood et al , ]. Since the model outputs cannot be used directly, we apply bias correction that corrects all moments of the climate fields' statistical distribution at monthly scale.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the WorldClim dataset is the best-developed dataset available for Nepal [20,42,43,53,54]. Moreover, a study by Glotter et al [55] showed that, once a correction is applied, the results of general circulation models and regional climate models are indistinguishable in all four scenarios. This suggests that, when developing impact assessments, the benefits that are generated by dynamically downscaling raw, general-circulation models may not be sufficient to justify the computational demand.…”
Section: Limitations Of the Date Setmentioning
confidence: 99%
“…These results can highlight the potential need for conservation strategies in water-limited regions. Other researchers have used RCM output to drive crop simulations in central Asia (Bobojonov and Aw-Hassan 2014) and the Midwestern U.S. (Glotter et al 2014) to examine the agronomic response to changes in regional climate. An integrated modeling continuum.…”
Section: Definition and Scopementioning
confidence: 99%